2003
DOI: 10.3171/foc.2003.15.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance spectroscopy of atypical diffuse pontine masses

Abstract: Object Diffuse pontine gliomas in children carry a dismal prognosis, with a mean survival of less than 1 year despite therapy. The diagnosis is based on the characteristic changes demonstrated on traditional magnetic resonance (MR) imaging. A few typically MR imaging–appearing pontine masses, however, do not behave in the expected fashion, which calls the original diagnosis into question. Methods The aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Our study included 6 patients (16%) whose overall survival was > 24 mo. This represents a larger proportion of long-term survivors when compared some studies [6], but is comparable to other cohorts reported in the literature [31, 52]. The majority of patients were referred to our institution following radiation therapy for evaluation after disease progression.…”
Section: Discussionsupporting
confidence: 75%
“…Our study included 6 patients (16%) whose overall survival was > 24 mo. This represents a larger proportion of long-term survivors when compared some studies [6], but is comparable to other cohorts reported in the literature [31, 52]. The majority of patients were referred to our institution following radiation therapy for evaluation after disease progression.…”
Section: Discussionsupporting
confidence: 75%
“…24 The evaluation of the prognostic value of PET data in intrinsic infiltrative brainstem lesions will require a larger and more homogeneous series. Indeed, the authors of a study conducted in a large series of patients have recently suggested that MR spectroscopy data might provide significant prognostic information in intrinsic infiltrative brainstem lesions, 13 contrary to MR contrast enhancement, which seems to present a very limited prognostic value in brainstem gliomas. 12 In our series, MR contrast enhancement was not correlated with FDG uptake level or extent.…”
Section: Additional Prognostic Informationmentioning
confidence: 99%
“…2,6,7,10,21,[25][26][27][28] Therefore, the management of these lesions requires careful consideration of the risk related to serial biopsy trajectories and the level of radiological diagnostic certainty. 7,12,13,26 It is common, however, to encounter intrinsic infiltrative brainstem lesions that cannot be diagnosed on the basis of imaging studies alone; the preoperative neuroimaging diagnosis may not be accurate for tumor type in approximately Results of positron emission tomography guidance and reassessment of the utility of and indications for stereotactic biopsy in children with infiltrative brainstem tumors 25%, and up to 13% of such lesions are nonneoplastic ones. 13,27,28 Therefore, the consequences of empirical therapy should not be underestimated before making appropriate treatment recommendations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…34 In this context, and particularly given the possibility of a nonneoplastic diagnosis, the standard practice of empirical radiation therapy has been questioned. 29,[35][36][37] Aside from the need for diagnostic certainty, there has been increased recognition that tissue samples will be needed for the development and testing of cutting-edge treatment options, including new chemotherapies, gene therapies, and immunotherapies. 25,38 New treatments are especially necessary for patients with DIPG for whom meaningful therapeutic options are limited, and some have argued that progress has been impeded by the lack of available tissue for analysis.…”
Section: Discussionmentioning
confidence: 99%